AB1106 PREVALENCE AND EPIDEMIOLOGY OF FAMILIAL MEDITERRANEAN FEVER AND TUMOR NECROSIS FACTORRECEPTOR-ASSOCIATED PERIODIC SYNDROME: RESULTS FROM AN ITALIAN CENTER. (June 2019) - Talotta, Rossella; Mosca, Lorena; Rucci, Francesco; Brucato, Antonio; Atzeni, Fabiola; Perno, Carlo Federico; Scaglione, Francesco; Cavallari, Ugo
Abstract : Background: Familial Mediterranean fever (FMF) and tumor necrosis factor (TNF) receptor-associated periodic syndrome (TRAPS) represent two forms of periodic monogenic autoinflammatory diseases, characterized by recurrent and auto-limiting attacks of fever and systemic inflammation. Both the diseases are due to the aberrant activation of inflammasome platforms. Several variants in the Mediterranean Fever (MEFV) gene and TNF Receptor Superfamily Member 1A (TNFRS1A) gene are respectively at the basis of FMF and TRAPS. Objectives: The aim of this study is to report the genotype and phenotype prevalence of a cohort of patients referring to our laboratory with a suspicious diagnosis of FMF or TRAPS. Methods: We retrospectively collected genetic and demographic data of patients undergoing MEFV (NM_000243) and TNFRS1A (NM_001065) genetic test at our laboratory. Both genes were analysed by direct sequencing on both strands. Data were statistically analysed for descriptive and inferential purposes. Results: A total of 168 cases were collected, most of which were Caucasian subjects (88.0%). The most common clinical manifestation was periodic fever, occurring in 121 cases, with musculoskeletal, intestinal and cutaneous symptoms, polyserositis and lymphadenopathy occurring at variable rates. Demographic and clinical characteristics are resumed in tab .1. MEFV genotyping, performed in 159 patients, identified 8 different pathogenic variants (p.Phe479Leu, p.Met680Ile, p.Met694Val, p.Met694Ile, p.Lys695Arg, p.Val726Ala, p.Ala744Ser, p. Arg761His), associated with different geographic provenience and symptoms ( tab .2, 4). Analysis of TNFRS1A gene in 80 subjects revealed the presence of the pathogenic variant p.Cys102Tyr in 3 patients (3.75%); tab. 3, 5. According to Eurofever scoring system, the MEFV variant p.Ala744Ser was significantly associated to the likelihood of having FMF and to the severity of the disease. A higher prevalence of MEFV pathogenic variants was observed in Egyptians and patients living in Southern Italy. Conclusion: Our data report MEFV and TNFRS1A genotypes identified in a cohort of patients referring to an Italian center, affected by periodic fever and other systemic symptoms. Only the MEFV variant p.Ala744Ser appeared to be significantly correlated with the Eurofever classification score. References: [1] Vitale A, Rigante D, Lucherini OM, De Palma A, Orlando I, Gentileschi S, Sota J, Simpatico A, Fabiani C, Galeazzi M, Frediani B, Cantarini L. The diagnostic evaluation of patients with a suspected hereditary periodic fever syndrome: experience from a referral center in Italy. Intern Emerg Med. 2017;12(5):605-611. [2] Federici S, Sormani MP, Ozen S, Lachmann HJ, Amaryan G, Woo P, Kon-Paut I, Dewarrat N, Cantarini L, Insalaco A, Uziel Y, Rigante D, Quartier P, Demirkaya E, Herlin T, Meini A, Fabio G, Kallinich T, Martino S, Butbul AY, Olivieri A, Kuemmerle-Deschner J, Neven B, Simon A, Ozdogan H, Touitou I, Frenkel J, Hofer M, Martini A, Ruperto N, Gattorno M; Paediatric Rheumatology International Trials Organisation (PRINTO) and Eurofever Project. Evidence-based provisional clinical classification criteria for autoinflammatory periodic fevers. Ann Rheum Dis. 2015;74(5):799-805. Disclosure of Interests: None declared